1994
DOI: 10.1165/ajrcmb.11.1.8018338
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition by dexamethasone of retinoic acid-induced enhancement of leukotriene C4 synthesis in rat basophilic leukemia-1 cells.

Abstract: We investigated inhibitory actions of dexamethasone (DEX) on retinoic acid (RA)-induced enhancement of leukotriene C4 (LTC4) synthesis in rat basophilic leukemia-1 (RBL-1) cells. Cultured cells were preincubated with RA for 16 h with or without DEX, and generation of LTC4 was measured by high performance liquid chromatography in cell-free and intact cell systems. RA (0.1 microgram/ml) significantly potentiated calcium ionophore-stimulated production of LTC4 synthesis. DEX inhibited the RA-induced enhancement o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

1995
1995
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…LTC 4 synthase, also an integral nuclear envelope protein sharing 31% amino acid identity with FLAP (25), conjugates LTA 4 to reduced glutathione to form LTC 4 . Although LTC 4 synthase is induced in U937 cells during differentiation into monocyte/macrophage-like cells in response to treatment with dimethyl sulfoxide (26) and in RBL-1 cells treated with retinoic acid (27) as assessed by an increase in enzyme activity, no information exists on the transcriptional or translational regulation of this terminal enzyme. The expression of LTC 4 syn- …”
Section: Resultsmentioning
confidence: 99%
“…LTC 4 synthase, also an integral nuclear envelope protein sharing 31% amino acid identity with FLAP (25), conjugates LTA 4 to reduced glutathione to form LTC 4 . Although LTC 4 synthase is induced in U937 cells during differentiation into monocyte/macrophage-like cells in response to treatment with dimethyl sulfoxide (26) and in RBL-1 cells treated with retinoic acid (27) as assessed by an increase in enzyme activity, no information exists on the transcriptional or translational regulation of this terminal enzyme. The expression of LTC 4 syn- …”
Section: Resultsmentioning
confidence: 99%
“…Four LT-synthesizing enzymes, cytosolic phospholipase A 2 (cPLA 2 ), 5-LO, LTA 4 hydrolase, and LTC 4 synthase (LTC 4 syn), and an essential protein, five-lipoxygenase activating protein (FLAP), are consecutively involved in the synthesis of LTB 4 and LTC 4 in this metabolic pathway. Recent in vitro studies have demonstrated that these enzymes and their protein molecules are transcriptionally and/or post-transcriptionally up-regulated by various bioactive substances including interleukins (ILs) (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). These findings suggest that these enzyme activities are controlled by similar molecular mechanisms in vivo and are possibly up-regulated in bronchial asthma in which ILs and other bioactive substances are activated.…”
Section: Introductionmentioning
confidence: 99%
“…RBL-1 cells produce LTC4 and LTB4 in amounts sufficiently large to be measured by high-performance liquid chromatography (HPLC) after induction of LTC4 synthase activity by treating with all /raw.s-retinoic acid (RA) at 0.1 ug/ml for 16 h and sub sequent stimulation with A23187 [13][14][15].…”
Section: Aterials and M Ethodsmentioning
confidence: 99%